Principles and practicalities for measuring child poverty in the rich countries - Miles Corak (Institute for the Study of Labor (IZA), 2005)
This paper has three objectives. The first is to discuss the major issues involved in defining and measuring child poverty. The choices that must be made are clarified, and a set of six principles to serve as a guide for public policy are stated. The second objective is to take stock of child poverty and changes in child poverty in the majority of OECD countries since about 1990 when the Convention on the Rights of the Child came into force. Finally, the third objective is to formulate a number of suggestions for the setting of credible targets for the elimination of child poverty in the rich countries. This involves a method for embodying the ideal of children having priority on social resources into a particular set of child poverty reduction targets, it involves the development of appropriate and timely information sources, and finally it involves the clarification of feasible targets that may vary across the OECD.
Keywords: I30; I32; I38; 330; poverty; children; social policy; Armut; Kinder; Messung; Armutspolitik; OECD-Staaten; Globalisierung; Außenhandelsliberalisierung; Internationale Arbeitsteilung; Internationale Wirtschaftsbeziehungen; Weltwirtschaftsordnung; Index; Messung; Indexberechnung; Welt